A Cultural History of Twin Beds - Hinds, Hilary (Home, 2019)
A Cultural History of Twin Beds challenges our most ingrained assumptions about intimacy, sexuality, domesticity and hygiene by tracing the rise and fall of twin beds as a popular sleeping arrangement for married couples between 1870 and 1970. Modern preconceptions of the twin bed revolve around their use by couples who have no desire to sleep in the same bed space. Yet, for the best part of a century, twin beds were not only seen as acceptable but were championed as the sign of a modern and forward-thinking couple. But what lay behind this innovation? And why did so many married couples ultimately abandon the twin bed?In this book, Hilary Hinds presents a fascinating insight into the combination of beliefs and practices that made twin beds an ideal sleeping solution. Using nuanced close readings of marriage guidance and medical advice books, furnishing catalogues, novels, films and newspapers, this volume offers an accessible and rigorous account of the curious history of twin beds. This is vital reading for those with an interest in cultural history, sociology, anthropology and psychology.